2022
DOI: 10.1007/s00170-022-09749-1
|View full text |Cite
|
Sign up to set email alerts
|

Helical milling for making holes on carbon fiber-reinforced polymer

Abstract: Carbon ber reinforced polymer (CFRP) is widely used in various elds due to its excellent properties.However, machining defects such as delamination and burr are still the key issues constraining highquality hole making on CFRP. This research takes the helical milling process to make holes on CFRP and two kinds of cutting conditions (dry cutting and jet cold air assisted cutting) are explored. Tool wear, cutting force, delamination and surface morphology are taken as the main indices to be analyzed. The in uenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sun et al [17] concluded that the cutting temperature produced by helical milling is lower than that of traditional drilling. Scholars found that axial feed is the most critical factor for generating thrust and the addition of bers has a signi cant impact on the cutting force [18][19]. It can be seen that compared with drilling, helical milling has obvious advantages in reducing the cutting temperature, reducing the cutting force and increasing the smooth chip removal, and reducing the damage of the entrance and exit [20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [17] concluded that the cutting temperature produced by helical milling is lower than that of traditional drilling. Scholars found that axial feed is the most critical factor for generating thrust and the addition of bers has a signi cant impact on the cutting force [18][19]. It can be seen that compared with drilling, helical milling has obvious advantages in reducing the cutting temperature, reducing the cutting force and increasing the smooth chip removal, and reducing the damage of the entrance and exit [20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced polymer (CFRP) has the characteristics of low specific gravity, high strength, and high temperature resistance, and has been widely used in aerospace and other fields [1][2][3]. However, CFRP has the characteristics of anisotropy and high brittleness, which makes it prone to defects such as burrs and tearing during processing [4,5]. Therefore, the hole quality of CFRP has become a key factor affecting the processing quality and performance of structural parts.…”
Section: Introductionmentioning
confidence: 99%
“…Helical milling is a feasible milling method for the large-diameter holes in hard materials [4,5] . The key cutting parameters such as spindle speed, feed speed, and pitch on cutting force are investigated and optimized for helical milling by Su et al [6] . Milling holes of materials with poor cutting performance requires high cutting force, which easily leads to high cutting temperature and serious tool wear.…”
Section: Introductionmentioning
confidence: 99%